Issues in Malaysia-Indonesia relations: 2000 – 2010 - Wan Shawaluddin Wan Hassan; Marja Azlima Omar; Abdul Rahman Tang Abdullah (Penerbit UMS, 2017)
Malaysia-Indonesia belongs to the Malay kinship or rumpun Melayu as they are immediate neighbouring countries. However, being sovereign nation states, they are bound to adhere to their respective national interests as the guiding principles in the relation with one another. This paper examines the ups and downs in Malaysia-Indonesia bilateral relations from 2000 to 2010. Among the issues included in the discussion are the role of ASEAN in Malaysia-Indonesia relations, cooperation in workforce and illegal immigrants, overlapping territorial claims, terrorism, trade and investment, border cooperation as well as issues pertaining to non-diplomatic matters such as tourism, social and cultural issues. The paper is constructed based on the data collected from interviews with diplomat and officers. It concludes that although both countries belong to the same Malay kinship, national interests of both countries are distinctly different from each other because both are independent sovereign states. Accordingly, the ways in which both countries manage contentious issues through diplomatic and non-diplomatic channels are predominantly determined by their own national interests. This is the pre-dominant reason that explains conflicting nature of bilateral relations between of the two countries in the past decade.